Objective method to evaluate the competency of residents in cardiac surgery. (17th January 2021) - Badreldin, Akmal M A; Muehle, Anja; Misic, Jovan; Tvildiani, Tamari; Duerr, Georg Daniel; Paulini-Heine, Beate; Peivandi, Ali Asghar
ABSTRACT:  : OBJECTIVES: Cardiac surgery training has become more challenging as patients and their diagnoses become more complex. Our goal was to develop a multicategorical assessment model for evaluating residents in cardiac surgery. This model is intended to ensure goal-directed progress in their training as well as to recognize and support their surgical talents. METHODS: We developed a new questionnaire in a multistage, 3-round process based on the Delphi method 'estimate-talk-estimate', using 55 competencies, including 38 general and 17 domain-specific competencies. Each competency is evaluated with 1 or more questions, to which 1 (not competent) to 6 (very competent) points can be chosen as an answer. RESULTS: The resulting model achieved 2 main goals: first, presenting a well-defined competency list for cardiac surgical training and second, providing an objective and realistic evaluation of trainees' abilities. Residents were assessed by all trainers to achieve a high level of objectivity. CONCLUSIONS: This evaluation model is highly objective, because residents are evaluated by multiple trainers. It allows individual support and enables better transparency in residency training. Talents and skills are evaluated, recognized and adopted as a base for individual feedback and personalized training programmes.